Screening of Lactic Acid Bacteria for the Purpose of Chitin Recovery Processing - SISWA SETYAHADI (Indonesian Society for microbiology, 2007)
Lactic acid fermentation has been studied as an alternative method of chitin recovery from the natural chitin compounds, such as shrimp waste. The purpose of this research was to identify a potential lactic acid bacterium which can produce large amount of lactic acid and has the ability to release chitin (demineralization) from shrimp-shell-waste. Among 11 bacteria tested, strain 15 was the strongest lactic acid producer yielding 1.09% (v/v) lactic acid in the media with a pH of 4.15 after 6 days incubation at 37 oC. After that, strains 17 and 23 produced 0.79 and 0.74% of lactic acid respectively. These three strains were selected for further experiments on various kinds of media using two-day incubation periods. No strains produced lactic acid well in MRS media containing lactose. The best medium for lactic acid production by strains 15 and 17 was MRS containing glucose, molasses or mixture of molasses and shrimp shell waste. Fermentation of shrimp shell waste using strain 15 caused an increase of viscosity reflecting an increase of soluble chitin in the media..